Analysis of Unity and Coherence in Writing Scientific Essay at the Fifth Semester Students of English Department FKIP UNILAK 2016/2017 Academic Year. - M. Fadhly Farhry Abbas; Herdi Herdi (J-SHMIC : Journal of English for Academic, 2017)
This research is based on the needs to analyze and evaluate students’ ability in applying unity and coherence aspect in a scientific essay. This is because unity and coherence aspect become important thing in a paragraph, essay, or other kinds of composition. This research aims at analyzing students’ ability in applying unity and coherence aspect in a scientific essay. 52 students at semester 5in 2016/2017 academic year of English Education Department Faculty of Teachers Training and Education University of Lancang Kuning were the participants in this study. Test and interview were used to collect the data. The data from the test was analyzed by using scoring rubric and the data from the interview was explained descriptively. The result showed that the students’ ability in applying unity and coherence was categorized into good level. The students’ average score was 74.9. Furthermore, from the interview, it can be stated that students were able to write an essay well with good unity and coherence. It was basically influenced by good understanding about unity and coherence. Then, the students did writing practice at leisure time more and more. In conclusion, it can be stated that the students’ ability in applying unity and coherence in writing a scientific essay is in good level with average score 74.9.